Reconstruction of Minimum Age for Marriage as a Form of Legal Protection for Women (Analysis of Constitutional Court Decision No. 22/PUU-XV/2017) - Nugraha, Xavier; Izzaty, Risdiana; Putri, Annida Aqiila (Universitas Negeri Semarang, 2019)
Article 7 paragraph (1) Law no. 1 of 1974 concerning Marriage provides that the minimum age for marriage for men is 19 years while for women is 16 years. In the explanation, this aims to maintain the health of husband and wife and offspring. However, the minimum age limit for marriage for women that has been set is contrary to Law no. 35 of 2014 concerning Child Protection which stipulates that a child is someone who is not yet 18 years old. So that makes Article 7 paragraph (1) Law No. 1 of 1974 is discriminatory and has the potential to violate the constitutional rights of girls with the occurrence of child marriage. Constitutional Court Decision No. 22/PUU-XV/2017 states that Article 7 paragraph (1) of Law no. 1 of 1974 has no permanent legal force and gives the legislature 3 years to formulate new norms. If this time period has passed, the minimum age limit for marriage will be harmonized with the age limit for children in Law no. 35 of 2014. The purpose of this study is to describe legal protection for women through setting a minimum age limit for marriage. The research method used is normative research with statutory, conceptual and case approaches.